2021
DOI: 10.1016/j.ymeth.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Methods in isolation and characterization of bovine monocytes and macrophages

Abstract: Monocytes and macrophages belong to the mononuclear phagocyte system and play important roles in both physiological and pathological processes. The cells belonging to the monocyte/macrophage system are structurally and functionally heterogeneous. Several subsets of monocytes have been previously identified in mammalian blood, generating different subpopulations of macrophages in tissues. Although their distribution and phenotype are similar to their human counterpart, bovine monocytes and macrophages feature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 170 publications
0
7
1
Order By: Relevance
“…Heat-stressed Holstein cows showed a decreasing tendency of monocyte populations in August compared with those in May. Monocytes are myeloid cells produced by the bone marrow that play important roles in the immune response, such as to infections and injuries [59]. Contrary to the results of this study, another study reported that monocyte counts increased in summer [60].…”
Section: Discussioncontrasting
confidence: 77%
“…Heat-stressed Holstein cows showed a decreasing tendency of monocyte populations in August compared with those in May. Monocytes are myeloid cells produced by the bone marrow that play important roles in the immune response, such as to infections and injuries [59]. Contrary to the results of this study, another study reported that monocyte counts increased in summer [60].…”
Section: Discussioncontrasting
confidence: 77%
“…In total (4.4 ± 0.83) × 10 6 BBMs were recovered from each 1-mL volume of bovine whole blood obtained from five individual cattle during approximately 2 months of culturing. Since normal bovine whole blood contains monocytes/macrophages at an average concentration of 4 × 10 5 cells/mL (Ceciliani et al, 2021), our data reveal that BBMs were efficiently proliferated using the coculture of whole blood with B46 cells. It is also likely that the endothelial features of B46 cells are effective at stimulating the proliferation of BBMs under coculturing conditions, as previously reported (Tanaka et al, 1993).…”
Section: Resultsmentioning
confidence: 76%
“…Whole blood from 6 clinically healthy pluriparous dairy cows was collected in sterile tubes with EDTA as an anticoagulant during routine slaughtering procedures. The peripheral blood mononuclear cells (PBMCs) were purified as previously reported from 60 mL of whole blood [ 23 ]. Briefly, the tubes were centrifuged at 1,260 g for 30 min at 18°C without brake, and the buffy coat was collected and diluted in cold PBS + 2 mM EDTA (1:2 dilution).…”
Section: Methodsmentioning
confidence: 99%